Embroidered Stories : Interpreting Women's Domestic Needlework from the Italian Diaspora - Sciorra, Joseph; Giunta, Edvige (Book collections on Project MUSE., 2014)
"For Italian immigrants and their descendants, needlework represents a marker of identity, a cultural touchstone as powerful as pasta and Neapolitan music. Out of the artifacts of their memory and imagination, Italian immigrants and their descendants used embroidering, sewing, knitting, and crocheting to help define who they were and who they have become. This book is an interdisciplinary collection of creative work by authors of Italian origin and academic essays. The creative works from thirty-seven contributors include memoir, poetry, and visual arts while the collection as a whole explores a multitude of experiences about and approaches to needlework and immigration from a transnational perspective, spanning the late nineteenth century to the late twentieth century. At the center of the book, over thirty illustrations represent Italian immigrant women's needlework. The text reveals the many processes by which a simple object, or even the memory of that object, becomes something else through literary, visual, performance, ethnographic, or critical reimagining. While primarily concerned with interpretations of needlework rather than the needlework itself, the editors and contributors to Embroidered Stories remain mindful of its history and its associated cultural values, which Italian immigrants brought with them to the United States, Canada, Australia, and Argentina and passed on to their descendants"--